Disaster Recovery Planning by Using Cloud Computing Technology - Hamdi, Nurul; Junidar, Junidar (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2016)
The development of digital data storage technology has opened up a new era. Previously, there are only offline data storage media such as hard drive in the computer hardware or portable flash disk that let us take them everywhere, yet the development of technology has been offering online data storage media known as Cloud Storage. As a company goes forward, the enterprise data also increase every year. Indeed, most companies which run a great business have to deal with the possibility of losing their important data during some unexpected situations, such as natural disaster, fire, or virus and warm attack against their system. Therefore, data protection that has the flexibility and support of the up-to-date storage array platforms is required for digital companies to manage a large amount of data. Cloud computing is a model that enables a support service named â€œEverything-as-a-serviceâ€ (XaaS). The Cloud is a computing model that integrates various elements with the scale and elasticity related to IT which aims to maximize the consumer service. Accordingly, companies are no longer bothered with the development of investment in the data center or others because it is provided as a service from the cloud provider. The use of Cloud Computing technology has a great role in reducing cost related to disaster recovery planning. The contribution is granted optimally by maximizing the infrastructure and computing resources, especially if the company uses web platform where the level of privacy and security of enterprise data becomes a major consideration. If disaster occurs, data will still be stored and the continuance of a company's business will not be disrupted.Keywords: cloud computing, disaster recovery planning